Socio-economic impact and quality of life of local community through homestay program / Nur Syuhada Shafika Muhd Mahyuddin, Siti Norfarahanim Che Adnan and Noraini Musa - Muhd Mahyuddin, Nur Syuhada Shafika; Che Adnan, Siti Norfarahanim; Musa, Noraini (2015)
Tourism is multi-sectors that consist of the accommodations, attractions, lodgings, foods and beverages, and other services. Thus, tourism industry can be seen as a bundle of tourism products and services. Therefore, the aim of this descriptive study is threefold: (a) to determine the socio economic impact of homestay program towards the local community and (b) to identify the quality of life affected to the local community through the homestay program. A self-administered questionnaire survey collected 100 respondents from the local communities around homestay program in Malacca. The title of this study is about the socio-economic impacts and quality of life of local community through homestay program. This study provides beneficial managerial and practical implications for local community, nongovernment sectors and government related authorities such as Ministry of Tourism and Culture and other stakeholders in order to achieve the benefits from the socioeconomic impacts to the communities’ quality of life.